2016
DOI: 10.1002/cad.20162
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Poverty and Cognitive Development in Latin America in the 21st Century

Abstract: For at least eight decades, researchers have analyzed the association between childhood poverty and cognitive development in different societies worldwide, but few of such studies have been carried out in Latin America. The aim of the present paper is to systematically review the empirical studies that have analyzed the associations between poverty and cognitive development in children under 18 years of age from Latin American and Caribbean countries between 2000 and 2015. This analysis takes into consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 61 publications
0
7
0
4
Order By: Relevance
“…Es de destacar el papel de la escuela en CSE bajo, en el que los estudiantes de alto DA alcanzan niveles similares de autorregulación que sus pares en CSE medio. Es decir, los efectos negativos que tiene la pobreza sobre el desarrollo (Segretin et al, 2016) y el DA (Hair et al, 2015) parecen compensarse en la escuela para los alumnos que consiguen un alto DA en CSE bajo.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Es de destacar el papel de la escuela en CSE bajo, en el que los estudiantes de alto DA alcanzan niveles similares de autorregulación que sus pares en CSE medio. Es decir, los efectos negativos que tiene la pobreza sobre el desarrollo (Segretin et al, 2016) y el DA (Hair et al, 2015) parecen compensarse en la escuela para los alumnos que consiguen un alto DA en CSE bajo.…”
Section: Discusión Y Conclusionesunclassified
“…Los efectos del CSE se recogen en distintos procesos implicados en el SRL y afectan negativamente a su desarrollo (Evans & Kim, 2013;Segretin, Hermida, Prats, Fracchia, Ruetti & Lipina, 2016), particularmente en: la planificación y memoria de trabajo (Hackman, Gallop, Evans & Farah, 2015). En bajo CSE los niños tienen menores desempeños cuando se requiere control de impulsos, demora de la gratificación y regulación emocional (Evans & Rosenbaum, 2008).…”
Section: Introductionunclassified
“…Several studies have documented differences in developmental skills between young children from high and low socio‐economic backgrounds both within and between countries (Fernald, Weber, Galasso, & Ratsifandrihamanana, ; Heckman, ; Paxson & Schady, ; Rubio‐Codina, Attanasio, Meghir, Varela, & Grantham‐McGregor, ; Wehby & McCarthy, ). This is especially evident in Latin America, one of the most economically unequal regions of the world, where children from lower resource areas consistently perform more poorly on developmental measures than children living in areas with greater resources (Schady et al, ; Segretin et al, ). Research has demonstrated that these early developmental gaps can persist or even widen over time, leading to long‐term adverse effects on educational and career attainment and hindering productivity at a national or regional level for the most affected areas of the world (Fernald et al, ; Paxson & Schady, ; Schady et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, we are struggling with a double burden of nutrition (undernutrition and obesity) (Perez-Escamilla et al, 2018). Both of them have been connected to poverty and cognitive development and learning (Segretin et al, 2016). More studies with a different conceptualization of poverty are needed to uncover the interrelationships (Lipina, 2017).…”
Section: Trends On Research On Mathematics Educationmentioning
confidence: 99%